Dying or Lying? For-Profit Hospices and End-of-Life Care - Gruber, Jonathan; Howard, David H.; Leder-Luis, Jetson; Caputi, Theodore L. (American Economic Review, 2025)
The Medicare hospice program is intended to provide palliative care to terminal patients, but patients with long stays in hospice are highly profitable, motivating concerns about overuse among the Alzheimer's and Dementia (ADRD) population in the rapidly growing for-profit sector. We provide the first causal estimates of the effect of for-profit hospice on patient spending using the entry of for-profit hospices over 20 years. We find hospice has saved money for Medicare by offsetting other expensive care among ADRD patients. As a result, policies limiting hospice use including revenue caps and antifraud lawsuits are distortionary and deter potentially cost-saving admissions. (JEL H51, I11, I12, I18, J14, L84)